PATRIARKIDIMATA BUDDHA, YESUS DAN MUHAMMAD: SUATU PENDEKATAN FEMINIS DALAM HISTORIOGRAFI AGAMA - george Junus aditjondro (Al-Qalam, 2008)
This writing aims to describe the ideology of patriarchy in three religions,Buddha, Christ, and Islam. This is using feminism perspective onhistoriography.This study indicates that the founding fathers of these three religions(Buddha, Jesus, and Muhammad) resist (with their own way) to thepatriarchy's culture. The revitalization of patriarchy's ideology andculture in these religion was conducted by the second generation (postprophetgeneration).